ANALYSIS OF DEVIATION IN SHORT-DURATION RAINFALL INTENSITY BASED ON ACTUAL RAINFALL FREQUENCY DATA USING THE MONONOBE METHOD - Gaoki, Karlin
The Mononobe method is commonly used for planning design rainfall intensity, such as in drainage systems, based on daily rainfall data. Alihough considered accurate for drainage system design, its reliability in estimating rainfall intensity over shorter intervals still needs to be evaluated. This research aims to assess the Mononobe method's ability to predict design rainfall intensity compared 1o actual rainfall over short intervals. The study processes 10-minute rainfall data from PT XYZ, which is then converted into 10-minute, 30-minute, 1-hour, 2-hour, and daily durations. Daily data is used to compare the use of partial and annual data series. Meanwhile, short-duration data is used to calculate actual rainfall intensity. The Gumbel distribution is applied in the processing of rainfall and intensity data. Frequency analysis compares the suitability of partial and annual series in determining design rainfall based on return periods. Additionally, the Mononobe intensity analysis tests the method's ability to estimate design rainfall intensity compared to actual intensity. The frequency analysis results show that the partial series data produces higher values, making it suitable for calculating design rainfall for return periods of 0 to 3 years. Beyond that, the design rainfall values from the annual series show higher values for return periods over 10 years. In the analysis of Mononobe's performance, it was found that the Mononobe intensity could estimate 10-minute rainfall intensity, with values 25-45% higher than the actual intensity. Howeverf,or rainfall durations of 30 minutes, I hour, and 2 hours, the Mononobe intensity is less optimal, as the actual intensity is 36-82% higher than the design intensity.